Thiamine Deficiency in a Developed Country: Acute Lactic Acidosis in Two Neonates Due to Unsupplemented Parenteral Nutrition. (August 2016) - Salvatori, Guglielmo; Mondì, Vito; Piersigilli, Fiammetta; Capolupo, Irma; Pannone, Veronica; Vici, Carlo Dionisi; Rizzo, Cristiano; Dotta, Andrea
Thiamine is a water-soluble vitamin implicated in several metabolic processes. Its deficiency, due to prolonged parenteral nutrition without adequate vitamin supplementation, can lead to multiorgan failure characterized by cardiovascular impairment and metabolic acidosis refractory to bicarbonate administration. Only thiamine administration allows the remission of symptoms. We report 2 preterm infants with acute thiamine deficiency due to prolonged parenteral nutrition without adequate vitamin supplementation.